Carbon Dots: An Innovative Tool for Drug Delivery in Brain Tumors - Giovanna Calabrese (MDPI AG, 2021)
Brain tumors are particularly aggressive and represent a significant cause of morbidity and mortality in adults and children, affecting the global population and being responsible for 2.6% of all cancer deaths (as well as 30% of those in children and 20% in young adults). The blood-brain barrier (BBB) excludes almost 100% of the drugs targeting brain neoplasms, representing one of the most significant challenges to current brain cancer therapy. In the last decades, carbon dots have increasingly played the role of drug delivery systems with theranostic applications against cancer, thanks to their bright photoluminescence, solubility in bodily fluids, chemical stability, and biocompatibility. After a summary outlining brain tumors and the current drug delivery strategies devised in their therapeutic management, this review explores the most recent literature about the advances and open challenges in the employment of carbon dots as both diagnostic and therapeutic agents in the treatment of brain cancers, together with the strategies devised to allow them to cross the BBB effectively.